Media power in digital Asia: Super apps and megacorps. (November 2022) - Steinberg, Marc; Mukherjee, Rahul; Punathambekar, Aswin
Tracing global shifts in ownership and conglomeration in the media and technology sectors, this introduction analyzes the emergence of the 'megacorp' and 'super app' as distinct forms and sites of media power. With a focus on Asia, we argue that the pairing of megacorps and super apps is driving the emergence of powerful digital companies that shape social, cultural, and political dynamics worldwide. Through analyses of companies including Reliance, SoftBank, Tencent, Alibaba, and Transsion, this special issue calls for a renewed engagement with theories of monopoly capital via the megacorp, and accounts of consumer and citizen experiences of this monopoly via a quotidian touch point, the super app. In conversation with scholarship on conglomerates, monopolies, and platforms as key institutional forms of media power, we show that media power in this digital conjuncture operates as much through national and regional differences as through the imperative to achieve a global scale.